Heavy duty port & industrial pavements innovations & case studies : delegate information pack : Wednesday, 16 June 1999 at the Forte Posthouse Hotel, Southampton. (Thomas Telford, 1999)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in Southampton 16 June 1999.
Keywords: Pavements -- Design and construction -- Congresses.; Harbors -- Access roads -- Congresses.; elektronické knihy; electronic books